A systematic review of consumer' perceived needs of health services related to osteoarthritis - Papandony, M.; Seneviwickrama, K.; Cicuttini, F.; Lasserre, K.; Teichtahl, A.; Wang, Y.; Briggs, Andrew; Wluka, A. (Elsevier, 2016)
Purpose: Osteoarthritis (OA), the most common cause of severe long-term pain and physical disability, is expected to be the fourth leading cause of disability by 2020. This will place a significant burden on health care and compromise quality of life. Effective management of OA requires active patient participation and involvement in management decisions. As health systems strive to provide consumer-centered care, it is important to identify consumers’ perceived needs regarding health care, to enable better matched service provision. The aim of this systematic review was to identify perceived needs relating to health services in people with OA. Methods: The published literature, indexed in MEDLINE, EMBASE, PsycINFO and CINAHL from 1990 - May 2015, was searched to identify patient perceived (i.e. the consumer perspective) health services needs related to OA. To capture all aspects of health services, the search included MeSH terms and text words comprehensively covering different health care providers, forms of health care, health care environments, barriers to care and access issues. A manual search of references related to potentially relevant review articles was also performed. Manuscripts were included if they provided information for people with, or with an interest in OA, regarding consumer perceived needs related to health services.Results: The combined search strategy returned 1051 papers, of which 16 articles were identified as relevant after limiting to English. Most of these studies were from the United Kingdom, United States of America or Australia. The majority of participants were recruited from general practice or subspecialty outpatient clinics and most studies involved only people with OA. Eight key themes emerged from the included studies relating to perceived health service needs of patients with OA: 1) patient-physician interaction, 2) pharmacologic therapy and pain management, 3) physiotherapy and exercise therapy, 4) complementary and alternative medicine (CAM), 5) joint replacement surgery, 6) access and waiting times, 7) health system interface and 8) other service needs. Whilst few studies focused on the study question, we were able to identify a number of important and consistent issues. Central to our findings was that patient motivation for seeking health services was predominantly driven by the desire for symptomatic relief and improved quality of life. Emphasis was placed on the need for health services to be disease-specific, effective and convenient in terms of mode of treatment and accessibility to the patient. Key aspects of desired health services included a multi-modal approach, including pharmacological management from a primary care physician and non-pharmacological therapies, such as physical therapy, and help addressing the psychosocial factors related to their condition. Patients expressed a need for help in coping with pain, disability, and the social and emotional impact of their disease. These areas were perceived as important in optimizing quality of life and function. Patients viewed a number of health services positively, with different health care providers providing complementary roles in management of OA. Conclusions: Health service use is driven by patient perceived need. As patients should be active participants in managing their OA, taking their perceived needs relating to health services into account when providing care is critical to enable coordinated, effective management of OA. This may enable better matching of health care and health information provision by service providers with patient perceived health care needs. Results of this systematic review have the potential to guide the direction of further work, and inform the provision of relevant services for those with OA, with the view to improving patient satisfaction, compliance, service and optimizing patient outcomes.